Pharmacological approaches to acute ischaemic stroke: reperfusion certainly, neuroprotection possibly - A R Green (2007)
Stroke is a major cause of both death and disability. However, there are no pharmacological treatments used in most countries other than recombinant tissue plasminogen activator, a thrombolytic, and this is only used in about 4% of patients presenting after an acute ischaemic stroke. One novel thrombolytic (desmoteplase) has just been reported to have failed in a Phase IIb/III trial, but other thrombolytics and reperfusion agents remain in development. The picture with neuroprotectant agents, that is compounds that act to preserve neurones following an acute cerebral ischaemic insult, is even more bleak. Despite the development of over 1,000 compounds, many proving effective in animal models of stroke, none has demonstrated efficacy in patients in the over 100 clinical trials conducted. This includes NXY-059, which was developed in accordance with the guidelines proposed by an academic-industry roundtable group (STAIR). This review examines the available data on compounds currently in development. It also proposes that the failure of translation between efficacy in preclinical models and patients is likely to terminate most current neuroprotective drug development. It is suggested that animal models must be made more representative of the patient condition (with other co-morbid conditions) and suggests that since stroke is primarily a cardiovascular disease with a neurological outcome, more research on the neurovascular unit would be valuable. New approaches on neuroinflammation, neurorestoration and neurorepair are also likely to gain prominence in the search for new drugs to treat this major clinical problem.